Morphologic Alterations Precede Functional Hepatic Impairment as Determined by 13C-Methacetin Liver Function Breath Test in Adult Fontan Patients - Schleiger, Anastasia; Kramer, Peter; Sallmon, Hannes; Jentsch, Niklas; Pileckaite, Marta; Danne, Friederike; Schafstedde, Marie; Müller, Hans-Peter; Müller, Tobias; Tacke, Frank; Jara, Maximilian; Stockmann, Martin; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objectives: Fontan-associated liver disease (FALD) is the most common end-organ dysfunction affecting up to 70-80 % of the Fontan population. The clinical significance of FALD is incompletely understood and no unambiguous correlation between hepatic function and FALD severity has been established. In this study, we sought to evaluate enzymatic liver function with liver maximum function capacity test (LiMAx®) in adult Fontan patients. Methods: Thirty-nine adult Fontan patients (median age: 29.4 years [IQR 23.4; 37.4], median follow-up after Fontan operation: 23.9 years [IQR 17.8;26.4]) were analyzed in a cross-sectional observational study using LiMAx® test (Humedics GmbH, Berlin, Germany), laboratory testing, transient elastography (TE) and hepatic ultrasound. The LiMAx® test is based on the metabolism of 13C-methacetin, which is administered intravenously and cleaved by the hepatic cytochrome P4501A2 to paracetamol and 13CO2, which is measured in exhaled air and correlates with functional liver capacity. Results: Hepatic enzymatic function assessed by LiMAx® test was normal in 28 patients (>315 µg/h*kg) and mildly to moderately impaired in 11 patients (140-314 µg/h*kg), while no patient displayed severe impairment of hepatic function (<139 µg/kg*h). No correlation was found between metabolic liver function and hepatic stiffness by TE (r²= -0.151; p=0.388) or the presence of sonographic abnormalities associated with FALD (r²=-0.204, p=0.24). There was, however, an association between enzymatic liver function capacity and the laboratory parameters bilirubin (r² = -0.333, p=0.009) and γ-glutamyl transferase. No correlation was detected between maximal liver function capacity and the severity of FALD (r²=-0.235; p=0.152). Conclusion: To the best of our knowledge, this is the first study to evaluate metabolic hepatic function using LiMAx® test in Fontan patients, which is a useful complementary diagnostic instrument to assess chronic hepatic injury. Metabolic hepatic function was preserved in most of our adult Fontan patients despite morphologic evidence of FALD. Moreover, metabolic hepatic function does not correlate with the extent of FALD severity evaluated by sonography or laboratory analysis. Thus, the development and progression of FALD in Fontan patients is not a uniform process and diagnostics of chronic hepatic injury during follow-up should encompass various modalities.